Analog performance of vertical nanowire TFETs as a function of temperature and transport mechanism. (October 2015) - Martino, Marcio Dalla Valle; Neves, Felipe; Ghedini Der Agopian, Paula; Martino, João Antonio; Vandooren, Anne; Rooyackers, Rita; Simoen, Eddy; Thean, Aaron; Claeys, Cor
Abstract: The goal of this work is to study the analog performance of tunnel field effect transistors (TFETs) and its susceptibility to temperature variation and to different dominant transport mechanisms. The experimental input characteristic of nanowire TFETs with different source compositions (100% Si and Si1− x Ge x ) has been presented, leading to the extraction of the Activation Energy for each bias condition. These first results have been connected to the prevailing transport mechanism for each configuration, namely band-to-band tunneling (BTBT) or trap assisted tunneling (TAT). Afterward, this work analyzes the analog behavior, with the intrinsic voltage gain calculated in terms of Early voltage, transistor efficiency, transconductance and output conductance. Comparing the results for devices with different source compositions, it is interesting to note how the analog trends vary depending on the source characteristics and the prevailing transport mechanisms. This behavior results in a different suitability analysis depending on the working temperature. In other words, devices with full-Silicon source and non-abrupt junction profile present the worst intrinsic voltage gain at room temperature, but the best results for high temperatures. This was possible since, among the 4 studied devices, this configuration was the only one with a positive intrinsic voltage gain dependence on the temperature variation.